Environmental micro‐niche filtering shapes bacterial pioneer communities during primary colonization of a Himalayas' glacier forefield. (18th November 2022) - Rolli, Eleonora; Marasco, Ramona; Fusi, Marco; Scaglia, Barbara; Schubotz, Florence; Mapelli, Francesca; Ciccazzo, Sonia; Brusetti, Lorenzo; Trombino, Luca; Tambone, Fulvia; Adani, Fabrizio; Borin, Sara; et al.
Abstract: The pedogenesis from the mineral substrate released upon glacier melting has been explained with the succession of consortia of pioneer microorganisms, whose structure and functionality are determined by the environmental conditions developing in the moraine. However, the microbiome variability that can be expected in the environmentally heterogeneous niches occurring in a moraine at a given successional stage is poorly investigated. In a 50 m 2 area in the forefield of the Lobuche glacier (Himalayas, 5050 m above sea level), we studied six sites of primary colonization presenting different topographical features (orientation, elevation and slope) and harbouring greyish/dark biological soil crusts (BSCs). The spatial vicinity of the sites opposed to their topographical differences, allowed us to examine the effect of environmental conditions independently from the time of deglaciation. The bacterial microbiome diversity and their co‐occurrence network, the bacterial metabolisms predicted from 16S rRNA gene high‐throughput sequencing, and the microbiome intact polar lipids were investigated in the BSCs and the underlying sediment deep layers (DLs). Different bacterial microbiomes inhabited the BSCs and the DLs, and their composition varied among sites, indicating a niche‐specific role of the micro‐environmental conditions in the bacterial communities' assembly. In the heterogeneous sediments of glacier moraines, physico‐chemical and micro‐climatic variations at the site‐spatial scale are crucial in shaping the microbiome microvariability and structuring the pioneer bacterial communities during pedogenesis.